Novel pathogenic VPS13A mutation in Moroccan family with Choreoacanthocytosis: a case report - Fatima Ouchkat; Wafaa Regragui; Imane Smaili; Hajar Naciri Darai; Naima Bouslam; Mounia Rahmani; Adyl Melhaoui; Yasser Arkha; Elmostafa El Fahime; Ahmed Bouhouche (BMC, 2020)
Abstract Background Choreoacanthocytosis (ChAc), is a rare neurodegenerative disease, characterized by movement disorders and acanthocytosis in the peripheral blood smears, and various neurological, neuropsychiatric and neuromuscular signs. It is caused by mutations in VPS13A gene with autosomal recessive pattern of inheritance. Case presentation Here we report two patients belonging to a consanguineous Moroccan family who present with movement disorder pathology. They were suspected to have choreoacanthocytosis according to biological, clinical and radiological finding. Thus, whole-exome sequencing was performed for precise diagnosis and identified a homozygous novel nonsense mutation c.337C > T (p.Gln113*) in exon 5 of VPS13A in the two affected siblings. Conclusion Here, we report a novel nonsense p.Gln113* mutation in VPS13A identified by whole-exome sequencing, which caused ChAc in a Moroccan family. This is the first description of ChAc in Morocco with genetic confirmation, that expands the mutation diversity of VPS13A and provide clinical, neuroimaging and deep brain stimulation findings.